Pencemaran Lingkungan Akibat Pengolahan Lumpur Tinja pada Instalasi Lumpur Tinja di Desa Tadukan Raga - Achmad Fajri Siregar; Nurhimmi Falahiyati; Akmal Samosir (LOCUS MEDIA PUBLISHING, 2026)
This study aims to analyze the management of fecal sludge at the Tungkusan Fecal Sludge Treatment Plant (IPLT) in Tadukan Raga Village and its impact on environmental pollution, focusing on the application of the principles of strict liability and polluter pays. This research employs an empirical juridical method with a qualitative approach through interviews, field observations, and document analysis. The results indicate that the management of the IPLT has not met the required technical and procedural standards, as evidenced by leakage in waste channels, unpleasant odors, and declining groundwater quality in nearby communities. The principles of strict liability and polluter pays have not been optimally implemented, resulting in the absence of compensation and environmental restoration efforts for affected residents. Key challenges include weak government oversight and limited human resources. This study recommends strengthening local regulations, improving managerial capacity, and consistently applying the polluter pays principle.